2009
DOI: 10.1111/j.1753-4887.2001.tb07021.x
|View full text |Cite
|
Sign up to set email alerts
|

The American Heart Association Dietary Guidelines for 2000: A Summary Report

Abstract: Recently, the American Heart Association published a revision of its dietary guidelines. The recommendations are based on new scientific findings, and address the contribution of growing rates of obesity, hypertension, and diabetes to heart disease in the United States. The guidelines for the general public are similar to dietary recommendations made by other health-related groups and government agencies and, therefore, place a greater emphasis on the adoption of healthy eating patterns and behaviors rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The dietary guidelines of the American Heart Association include specific recommendations tailored to an individual's risk of heart disease and stroke that are based on an analysis of hundreds of studies (28) . This recommended diet provides a generous amount of micronutrients essential for good health; however, a very small percentage of the population follows it.…”
Section: Nutrition and Strokementioning
confidence: 99%
“…The dietary guidelines of the American Heart Association include specific recommendations tailored to an individual's risk of heart disease and stroke that are based on an analysis of hundreds of studies (28) . This recommended diet provides a generous amount of micronutrients essential for good health; however, a very small percentage of the population follows it.…”
Section: Nutrition and Strokementioning
confidence: 99%
“…Decrease in body weight was reported as result of counselling. [28] It was reported that obesity, increased BMI, and waist-hip ratio were the contributing factors towards the increased risk of cardiovascular disease. [25] Excess adiposity was most important predictor of diabetes and CVD.…”
Section: Anthropometric Measuresmentioning
confidence: 99%
“…Based on several scientific articles that focus on the role of nutrition in health, a number of different organizations, including the WHO, the Institute of Medicine's Food and Nutrition Board and the European Food Safety Authority, issue and periodically update dietary recommendations and guidelines in order to assist the public with avoiding unhealthy lifestyles and preventing such chronic diseases as obesity, diabetes mellitus, CVD, osteoporosis and several cancers related to diet (3)(4)(5)(6) . Most guidelines offer recommendations regarding amounts and food types that should be consumed depending on age, gender and whether or not an individual is lactating or pregnant; these recommendations serve to help individuals maintain or improve their health.…”
mentioning
confidence: 99%